-6t+12-3t=18

Simple and best practice solution for -6t+12-3t=18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6t+12-3t=18 equation:


Simplifying
-6t + 12 + -3t = 18

Reorder the terms:
12 + -6t + -3t = 18

Combine like terms: -6t + -3t = -9t
12 + -9t = 18

Solving
12 + -9t = 18

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -9t = 18 + -12

Combine like terms: 12 + -12 = 0
0 + -9t = 18 + -12
-9t = 18 + -12

Combine like terms: 18 + -12 = 6
-9t = 6

Divide each side by '-9'.
t = -0.6666666667

Simplifying
t = -0.6666666667

See similar equations:

| (3+10)+(-9)=13 | | 2-6x+5x=-10 | | 4w-2w+6=3w-12 | | 0.5x-3.7=0.3 | | 0.5x-3.7=0.7 | | (52+48+57+62+68+y)/6=59 | | (80+4).2=84 | | 90=2(7x+1)-3x | | 2x+12-x=14 | | 3(2x+9)=-18+33 | | -(4-x)=3/4(x+7) | | 10x-5=-8x+13 | | 304=-8(-6x+4) | | 6-(2x-8)=4-3x | | 14-3x=x+2 | | 14=7x-2x+9 | | x+x-150=180 | | -16+-10x=7x+18 | | 7-(4x-2)=8-5x | | 5+x-5x=-11 | | x+x/5=180 | | 15x+5x=6x | | 9(w-4)=8(7+w) | | 5.25Z-2.01=-8.94 | | 22+65=4+25 | | -34+3x=14-3x | | -8(x-8)-5=59 | | 8=-3x+2 | | 7(x-3)=7+6x | | 2x-6-3x=2 | | 15-.75g=13-50g | | e^3x+1=20 |

Equations solver categories